Improving Students' Mathematical Comprehension and Curiosity Through Deep Learning Cycle Learning with The Help of Proprofs - Muhammad Fahmi Nurfadhilah; Agus Hikmat Syaf; Yayu Nurhayati Rahayu (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
This research is a quasi-experimental study that aims to investigate the effectiveness of the Deeper Learning Cycle (DELC) model supported by ProProfs media in improving students’ mathematical comprehension and curiosity. The objectives of the study include: (a) describing the implementation of the Deeper Learning Cycle (DELC) model assisted by ProProfs, (b) analyzing the improvement and acquisition of students' mathematical understanding, and (c) investigating the increase in students’ mathematical curiosity before and after the learning process. The study was carried out at MTs Mathla’ul Huda Baleendah, involving class VIIA as the experimental group and class VIIB as the control group, employing a nonequivalent control group design. The findings indicate that: (1) the implementation of the Deeper Learning Cycle (DELC) model assisted by ProProfs was executed very effectively; and (2) the enhancement and attainment of mathematical understanding in the experimental group were significantly greater than those in the control group; and (3) there was a notable increase in students’ mathematical curiosity after the implementation. These findings suggest that integrating the Deeper Learning Cycle (DELC)  model with ProProfs media is effective in fostering meaningful and engaging mathematics learning.